tính (-25)-13+|-15|-(-25)+(-13)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{17}{8}-\dfrac{13}{25}-\dfrac{12}{25}+\dfrac{15}{8}=\dfrac{17+15}{8}+\dfrac{-13-12}{25}=\dfrac{32}{8}+\dfrac{-25}{25}=4-1=3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
$25\frac{2}{13}-(\frac{15}{17}+15\frac{2}{13)$
$=25+\frac{2}{13}-\frac{15}{17}-15-\frac{2}{13}$
$=(25-15)+(\frac{2}{13}-\frac{2}{13})-\frac{15}{17}$
$=10-\frac{15}{17}=\frac{155}{17}$
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(\begin{array}{l}A = \dfrac{{ - 3}}{{14}} + \dfrac{2}{{13}} + \dfrac{{ - 25}}{{14}} + \dfrac{{ - 15}}{{13}}\\A = \left( {\dfrac{{ - 3}}{{14}} + \dfrac{{ - 25}}{{14}}} \right) + \left( {\dfrac{2}{{13}} + \dfrac{{ - 15}}{{13}}} \right)\\A = \dfrac{{ - 3 + \left( { - 25} \right)}}{{14}} + \dfrac{{2 + \left( { - 15} \right)}}{{13}}\\A = \dfrac{{ - 28}}{{14}} + \dfrac{{ - 13}}{{13}}\\A = - 2 + (-1)\\A = - 3\end{array}\)
b,
Cách 1:
\(\begin{array}{l}B = \dfrac{5}{3}.\dfrac{7}{{25}} + \dfrac{5}{3}.\dfrac{{21}}{{25}} - \dfrac{5}{3}.\dfrac{7}{{25}}\\B = \left( {\dfrac{5}{3}.\dfrac{7}{{25}} - \dfrac{5}{3}.\dfrac{7}{{25}}} \right) + \dfrac{5}{3}.\dfrac{{21}}{{25}}\\B = 0 + \dfrac{5}{3}.\dfrac{{21}}{{25}}\\B = \dfrac{{5.21}}{{3.25}}\\B = \dfrac{7}{5}\end{array}\)
Cách 2:
\(B = \dfrac{5}{3}.\dfrac{7}{{25}} + \dfrac{5}{3}.\dfrac{{21}}{{25}} - \dfrac{5}{3}.\dfrac{7}{{25}}\\B = \dfrac{5}{3}.({\dfrac{7}{{25}} -\dfrac{7}{{25}} + \dfrac{{21}}{{25}}})\\B = \dfrac{5}{3}.\dfrac{{21}}{{25}}\\B = \dfrac{{5.21}}{{3.25}}\\B = \dfrac{7}{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
b)(1-3-5+7)+(9-11-13+15)+...+(2009-2011-2013+2015)
=0+0+...+0
=0
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{25^5+25^7+25^9}{5^{11}+5^{13}+5^{15}+5^{17}+5^{19}+5^{21}}\)
\(=\dfrac{5^{10}+5^{14}+5^{18}}{5^{11}+5^{13}+5^{17}+5^{19}+5^{21}}\)
\(=\dfrac{5^{10}\left(1+5^4+5^8\right)}{5^{11}\left(1+5^2+5^4+5^6+5^8+5^{10}\right)}\)
\(=\dfrac{1+5^4+5^8}{5+5^3+5^5+5^7+5^9+5^{11}}\)
\(=\dfrac{1+5^4+5^8}{\left(5+5^5+5^9\right)+\left(5^3+5^7+5^{11}\right)}\)
\(=\dfrac{1+5^4+5^8}{\left(1+5^4+5^8\right)\left(5+5^3\right)}\)
\(=\dfrac{1}{5+5^3}\)
\(=\dfrac{1}{130}\)
\(\)
=-25-13+15+25-13
=(-25+25)+(15-13-13)
=0+2-13
=-(13-2)
=(-11)